Pengaruh Pengalaman Kerja dan Motivasi Kerja Terhadap Literasi Keuangan Pada Karyawan CV Berkah Saintek - Ari Wahyu Leksono (Jurnal Ilmiah Wahana Pendidikan, 2021)
Financial literacy for all employees is very necessary. Financial literacy skills have a strategic role in improving one's financial understanding. If a person does not have financial literacy, then he will find several difficulties, such as mismanaging money, getting entangled in moneylenders and fraud so that he suffers big financial losses. Work motivation and work experience are variables that will be investigated whether there is an effect on financial literacy. This study aims to describe the effect of work experience on financial literacy, the effect of work motivation on financial literacy and the effect of work experience and work motivation simultaneously on financial literacy. Respondents in this study were employees of CV Berkah Saintek Depok. The number of respondents as many as 43 employees. Research methods with quantitative methods. The data were processed by classical tests, such as heteroscedasticity test and multicollinearity test. After being tested classically, the data was continued with multiple regression test. The data was processed using SPSS 21. The results showed that work experience and work motivation had an effect on financial literacy, work experience had an effect on financial literacy and work motivation had an effect on financial literacy.